PENGARUH MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN METODE SCRAMBLE TERHADAP HASIL BELAJAR IPS SISWA KELAS III SDN 136 PEKANBARU - Indah Oktaviani; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: Influence of cooperative learning model by using scramble method toward learning result of IPS student class III SDN 136 Pekanbaru. The purpose of this study is to determine the effect of cooperative learning model using scramble method of learning outcomes IPS student class III SDN 136 Pekanbaru. The method used in this research that researchers use in this study is quasi exsperimental design. Based on the data analysis obtained the average result of the final test (post-test) control class 63,12 and the average of the final test (post-test) exsperimental class 71.85 obtained tcountof 3,02 and ttable of 1,997 which means tcount >table (3,02 >1,997). And from the result of correlation calculation of 0,6539 with strong influential category. This means that the use of cooperative learning model using scramble method gives a strong influence on the students learning outcomes in learning social sciences in third grade of elementary school 136 Pekanbaru.Key Words : Scramble , Learning Result Of Social Sciences